Analisis Potensi Sumber Daya Manusia Dalam Bisnis Akomodasi Pondok Wisata Di Desa Wisata Besani - Sofiani, Sofiani; Yulius, Kevin Gustian; Hardjasa, Gracia Eugene (Jurnal Ilmiah Global Education, 2024)
This research analyzes the potential of human resources in the accommodation business of pondok wisata or homestays in Besani Tourism Village, Blado District, Batang Regency, Central Java. Cottage tourism is a form of accommodation that offers more intimate lodging close to local communities, providing a different and satisfying experience for travelers seeking authenticity and togetherness in their journeys. The village stands out due to its concept of Javanese-Chinese cultural acculturation and attractive natural tourism potential. Through qualitative approaches and case studies, involving stakeholders as respondents, and utilizing primary data from interviews and observations, as well as secondary data from scientific literature and official documents. The SOAR approach is used to identify internal strengths, external opportunities, aspirations, and desired outcomes in accommodation business development. The analysis highlights the traditional skills of residents, significant tourism demand, and support from local government and companies. Human resource development strategies are recommended, including business management skills training, group-based cottage tourism development, service standard enhancement, income diversification, and local cultural promotion. This study provides insights into the potential of human resources to enhance competitiveness and sustainability in the tourism sector in Besani Tourism Village.